Mineiros e engenheiros: memória, identidade e trabalho nas Minas do Camaquã entre 1970 e 1996 - Nogueira, Jader Escobar (2012)
This research has as its objective to make a historical reconstruction of memory aspects, identity construction and working conditions of the miners and engineers of the Camaquã mines between 1970 and 1996. Many companies built facilities aiming at making economically possible the ore copper exploration in the region. In the 1940‟s, the state investment gave support for the creation of the Companhia Brasileira de Cobre, pressing a certain regularity for this economic activity. Transiting in the public and private sphere, the enterprise kept itself active until 1996. In this context, this research brings contributions not only for the local history construction, but also for a complimentary analysis of the mining activity in a national level. The identity formation in common of the miners and their working relations inside the galleries are analyzed, as a bibliographical review and reflections about the class concept and its existence among the workers are carried out. Thus, it was possible, supported in the Oral History methodology, the memory and culture reconstruction of the workers of the Camaquã Mines, located in Caçapava do Sul/RS/Brazil, through a daily life analysis of the involved in the historical process in question.